Commentary : the idea on motion (actual motion) in 3-Dimensional visual art / Hilal Mazlan - Mazlan, Hilal (Universiti Teknologi MARA, Perak, 2019)
Many people thought that motion in art began when Alexander Calder introduce his colourful, whimsical abstract public sculptures, among his sculptures are Red Mobile (1956) and Trepeid (1972). Actually, actual motion or movement in art has begun in 1919 when Naum Gabo introduces his work Kinetic Construction Standing Wave. Kinetic Construction (Standing Wave) was initially created by Naum Gabo to demonstrate kinetic energy to a class. Here a metal strip stand is mechanized to create a motion that produces the illusion of volume. In the early 20th century, artists became fascinated by speed and machinery. One technique they used was to show a single moving figure with many superimposed positions. Marcel Duchamp's Nude Descending a staircase (1912) was directly influenced by the photographs of Etienne-Jules Marey A Sword Thrust (1895). In the Futurist era (1909- late 1920s), motion or movement has been a great influence due to the industrial revolution. Artist frequently display motion in their artwork by showing multiple image or blurry motion. In his work Kinetic Construction (Standing Wave), Naum Gabo at first was trying to demonstrate to his student about constructivist ideas. It took Gabo nearly 3 years to complete this concept. This work elaborates so much about volume, time and space. He (Gabo) always talks about the important of controlling space in sculpture.